2019
DOI: 10.3390/ma12081252
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Immobilized onto Zirconia–Silica Hybrid Doped with Cu2+ as an Effective Biocatalytic System for Decolorization of Dyes

Abstract: Nowadays, novel and advanced methods are being sought to efficiently remove dyes from wastewaters. These compounds, which mainly originate from the textile industry, may adversely affect the aquatic environment as well as living organisms. Thus, in presented study, the synthesized ZrO2–SiO2 and Cu2+-doped ZrO2–SiO2 oxide materials were used for the first time as supports for laccase immobilization, which was carried out for 1 h, at pH 5 and 25 °C. The materials were thoroughly characterized before and after la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 60 publications
0
15
0
2
Order By: Relevance
“…In this study, the improved behavior was attributed to the hydrophobic/hydrophilic interaction of the nanoparticles [ 57 ]. Similar studies demonstrated dye removal efficiencies in the range of 30% to 100% [ 25 , 26 , 59 ]. However, such levels of removal have been mainly achieved on batch processes with longer removal times than ours (i.e., in the scale of hours).…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In this study, the improved behavior was attributed to the hydrophobic/hydrophilic interaction of the nanoparticles [ 57 ]. Similar studies demonstrated dye removal efficiencies in the range of 30% to 100% [ 25 , 26 , 59 ]. However, such levels of removal have been mainly achieved on batch processes with longer removal times than ours (i.e., in the scale of hours).…”
Section: Discussionmentioning
confidence: 64%
“…Some of the preferred materials for immobilization include macroscopic materials, such as metal oxides, natural polymers, and some minerals, as well as nanomaterials, such as magnetite, gold, and silica [ 11 , 21 , 23 , 24 ]. Other recent reports have demonstrated that by immobilizing laccases, the rate of dye degradation increases considerably [ 25 , 26 ]. For instance, the immobilization of laccase on materials, such as Zirconia-Silica Hybrid Doped with Cu +2 , is an attractive route for decolorization of the Remazol Brilliant Blue R dye [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the detailed activity recovery and laccase loading capacity data provided the information about immobilization behavior of α-Cellulose-Fe3O4-CTNs-SH. The significant laccase loading obtained by α-Cellulose-Fe3O4-CTNs-SH was quite high among the recently reported materials [33,46,[54][55][56][57][58][59][60][61]. Thus, the developed α-cellulose based material has significant potential to look like an enzyme immobilization material.…”
Section: Activity Recovery and Laccase Loading Capacity Evaluationsmentioning
confidence: 91%
“…In addition to proper immobilization method, suitable supports for targeted enzyme was also essential for immobilization (Dong et al, 2019b;Jankowska et al, 2019). In order to gain higher enzyme loading capacity and biocatalytic activity, it is always highly desirable to invent novel supports with high-performance (Antecka et al, 2018;Elizarova and Luckham, 2018;Zdarta et al, 2019;Jankowska et al, 2020).…”
Section: Introductionmentioning
confidence: 99%